2013
DOI: 10.1075/lic.13.1.01bis
|View full text |Cite
|
Sign up to set email alerts
|

Changing conventions in German causal clause complexes

Abstract: This paper contributes to the field of diachronic corpus studies of linguistic change through language contact in translation by replicating Becher’s (2011) study which found a trend from hypotaxis to parataxis in concessive clause complexes of German popular scientific articles, and examining whether a comparable trend can be found in causal clause complexes in another genre. The study draws on a one-million-word translation corpus of English business articles and their German translations, as well as on a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…This result is probably related to changing preferences in Present-Day German. Evidence of an increased German tendency of using parataxis rather than hypotaxis for causal clauses has been observed both for popular science by Becher (2011) and for business articles by Bisiada (2013), and both in original texts and translations. Becher (2011: 199) explains this trend towards parataxis with reference to readability.…”
Section: German and Swedish Translations Of English Supplementive Ingmentioning
confidence: 99%
See 2 more Smart Citations
“…This result is probably related to changing preferences in Present-Day German. Evidence of an increased German tendency of using parataxis rather than hypotaxis for causal clauses has been observed both for popular science by Becher (2011) and for business articles by Bisiada (2013), and both in original texts and translations. Becher (2011: 199) explains this trend towards parataxis with reference to readability.…”
Section: German and Swedish Translations Of English Supplementive Ingmentioning
confidence: 99%
“…The main difference between the target languages, i.e. the greater German use of main clauses, is probably a reflection of the ongoing German change towards parataxis identified by Becher (2011) andBisiada (2013). So far the results have only concerned translations from English.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has found that German language users do not increasingly prefer paratactic over hypotactic constructions. Though the use of hypotaxis in concessive constructions has decreased more strongly than in causal constructions (Bisiada 2013), it continues to be used frequently.…”
Section: Discussionmentioning
confidence: 99%
“…Some of those studies have reported a cross-linguistic increase in popularity of coordinated, paratactic structures, at times at the expense of hypotaxis, and attributed this shift to the status of English as a lingua franca (Musacchio 2005;Becher 2011;Bennett 2011, Bennett 2013Hansen-Schirra 2011;Bisiada 2013). However, despite the absence of structurally marked subordination, English can often be shown to exhibit a more hierarchical and subordinated structure characteristic of a hypotactic style than German does (Fischer 2007: 397, Fischer 2013Bisiada 2014).…”
Section: Structural Effects Of Language Contact In Translationmentioning
confidence: 99%